All Days 2014
DOI: 10.2118/169662-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of Ionic Effect of Smart Water for Enhancing Oil Recovery in Carbonate Reservoirs

Abstract: Enhanced oil recovery by smart waterflooding represents an implementable and attractive emerging oil recovery technology. For sandstone reservoirs, smart waterflooding has shown an outright incremental oil recovery in most laboratory and field tests while some promising experimental data have been presented from carbonates. It seems more difficult to assume a favorable performance for some reservoir formation a priori while dismissing the other, so more data and better understanding of the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 41 publications
7
55
0
Order By: Relevance
“…It was observed that none of the effluent samples had any insoluble salt fractions present (as shown in Figure 7). Thus no precipitate was observed in the effluent vials (Awolayo et al 2014). All mobile fines must have got dissolved as solubility of anhydrite increase significantly with decrease in temperature.…”
Section: Data Set 4: (Awolayo Et Al 2014)mentioning
confidence: 92%
See 3 more Smart Citations
“…It was observed that none of the effluent samples had any insoluble salt fractions present (as shown in Figure 7). Thus no precipitate was observed in the effluent vials (Awolayo et al 2014). All mobile fines must have got dissolved as solubility of anhydrite increase significantly with decrease in temperature.…”
Section: Data Set 4: (Awolayo Et Al 2014)mentioning
confidence: 92%
“…In data set 4 lime stone reservoir core plugs was flooded with 3 different brines of varied SO 4 2concentration (Awolayo et al 2014). For first 10 PV, high salinity formation water was introduced.…”
Section: Data Set 4: (Awolayo Et Al 2014)mentioning
confidence: 99%
See 2 more Smart Citations
“…2011). For carbonate reservoirs it has also been shown that increase in SO 4 2-concentration is associated to oil recovery only up to an optimum concentration, beyond which no additional oil recovery is observed (Awolayo et al 2014).…”
Section: Introductionmentioning
confidence: 99%